Karyotype analysis in lignosus bean (Dipogon lignosus) and lablab bean (Lablab purpureus) (Journal of the Bangladesh Agricultural University, 2011)
The experiment was conducted in the cytogenetics laboratory of the Department of Genetics and Plant Breeding of Bangladesh Agricultural University during July 2008 to September 2009 aiming to analyze and compare the karyotypes of two genotypes of Lignosus bean (Dipogon lignosus L.) and Lablab bean (Lablab purpureus L.). Root tips from germinated seeds were collected, pretreated and fixed in acetic alcohol for using in slide preparation. Chromosome measurements were done from the prints of the photomicrographs of prometaphase plates. In both the genotypes, 2n = 22 chromosomes was found. The range of length of the individual chromosome was 1.22 to 2.17μ in Lignosus bean, and 1.17 to 3.00μ in Lablab bean. In the Lignosus bean genotype, the haploid complement consisted of 11 metacentric (m) chromosomes with 3 individually identifiable ones but incase of Lablab bean the haploid complement consisted of 11 m chromosomes with 5 individually identifiable ones. All identifiable chromosomes were metacentric. This karyotype analysis of Lignosus bean and Lablab bean will be useful for further genetic studies. Keywords: Chromosomal characteristics; Karyotype analysis; Bean; Derivation DOI: http://dx.doi.org/10.3329/jbau.v9i1.8740 JBAU 2011; 9(1): 27-36